Vascular Endothelium as a Target of Immune Response in Renal Transplant Rejection - Piotti, Giovanni; Palmisano, Alessandra; Maggiore, Umberto; Buzio, Carlo (Frontiers in Immunology, 2014)
This review of clinical and experimental studies aims at analysing the interplay between graft endothelium and host immune system in renal transplantation, and how it affects the survival of the graft. Graft endothelium is indeed the first barrier between self and non-self that is encountered by host lymphocytes upon reperfusion of vascularised solid transplants. Endothelial cells express all the major sets of antigens that elicit host immune response, and therefore represent a preferential target in organ rejection. Some of the antigens expressed by endothelial cells are target of the antibody-mediated response, such as the AB0 blood group system, the HLA and MICA systems, and the endothelial cell-restricted antigens; for each of these systems, the mechanisms of interaction and damage of both preformed and de novo donor-specific antibodies are reviewed along with their impact on renal graft survival. Moreover the rejection process can force injured endothelial cells to expose cryptic self-antigens, toward which an auto-immune response mounts, overlapping to the allo-immune response in the damaging of the graft. Not only are endothelial cells a passive target of the host immune response, but also an active player in lymphocyte activation; therefore their interaction with allogenic T-cells is analysed on the basis of experimental in vitro and in vivo studies, according to the patterns of expression of the HLA class I and II and the co-stimulatory molecules specific for cytotoxic and helper T-cells. Finally, as the response that follows transplantation has proven to be not necessarily destructive, the factors that foster graft endothelium functioning in spite of rejection, and how they could be therapeutically harnessed to promote long-term graft acceptance, are described: accommodation that is resistance of endothelial cells to donor-specific antibodies, and endothelial cell ability to induce Foxp3+ Regulatory T-cells, that are crucial mediators of tolerance.